PENGARUH ZAT EKSTRAKTIF KAYU GAMAL (Gliricidia sepium Jacq.) TERHADAP NILAI KALOR - Rahmi Mauladdini; Wasrin Syafii; Deded Sarip Nawawi (BRIN Publishing, 2022)
The development of gamal wood (Gliricidia sepium Jacq.) aims to meet the needs of biomass energy in rural areas. Manystudies on extractives of gamal wood have been carried out, but there is very little information about the effect of extractives on thecalorific value. The effect of extractives on the calorific value can be determined by analyzing extractives compounds contained in thewood. This study aimed to determine the extractives compounds that affect the wood calorific value. The sawdust of gamal bark andwood was extracted by successively maceration by using solvents with different polarities. The free-extractives sawdust was thenmeasured for its calorific value. To ascertain the effect of extractives on the calorific value, the extract of the gamal bark and woodwas added to the oil palm sawdust, then the increase in calorific value was measured. The results showed that the extractives ingamal bark and wood affect the change of calorific value. The removal of extractives by using different solvents caused a differentdecrease in calorific value. The highest decrease in calorific value (4.03%) was obtained by non-polar (n-hexane) soluble extractiveof the gamal bark. The addition of gamal wood extracts to oil palm sawdust also causes an increase in the calorific value.Phytochemical and LC-MS/MS analysis of n-hexane soluble extractives from gamal bark detected groups of terpene compounds,amides alkaloids, flavonoids, coumarins, and benzopyrans. Based on the results of this study, the n-hexane soluble compounds wassuspected to have the most influence on the calorific value.